El periodo de adaptación y su influencia en el desarrollo psicosocial del niño/as de educación inicial paralelo “c” de la Unidad Educativa “Vicente León” ubicado en la provincia de Cotopaxi cantón Latacunga parroquia Juan Montalvo durante el año lectivo 2014-2015 - Chacón Chacón, Digna Piedad (2015)
Many institutions focus on the educational and social development of children, currently the adjustment period is not only a time to be met, the opposite is the time in which the child will know their culture, new people, spaces where the infant will strengthen its values, customs. It has been found that if the nursery lack motivation to perform recreational activities during the period of adaptation have difficulties in teaching socialization with peers, in many cases toddlers manifest problems in cognitive development, are shy and aggressive. The teaching methodology applied in the adjustment period has to be dynamic and entertaining for children and that based on this they can interact freely in all activities undertaken. It is very essential to have teaching resources in the classroom and more how to use them during the implementation of the recreational games, which allow us to reach the knowledge to infants.